APLIKASI KRIPTOGRAFI UNTUK MENGAMANKAN FILE AUDIO VIDEO MENGGUNAKAN VISUAL BASIC .NET - Frenky Fernando; Siswanto Siswanto; Eko Suryana (UNIVED Press, 2014)
In terms of file security is often diminished, because the file with the extension * and * .MP4 .MP3 is like the audio files that we secured was listening to the audio exams and video UAN English as exam for student/student in Ja Al-Haq is not given a security so that everyone can see the file. Application of cryptography to secure audio video files using visual basic Net made to secure the audio video files which are air-extension